2007
DOI: 10.1074/jbc.m610185200
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin Induces Cyclin D1 Degradation to Cause Cell Cycle Arrest through a Phosphatidylinositol 3-Kinase/AKT/GSK-3β Pathway and Is Antagonized by Insulin-like Growth Factor 1

Abstract: Myostatin is a transforming growth factor ␤ superfamily member and is known as an inhibitor of skeletal muscle cell proliferation and differentiation. Exposure to myostatin induces G 1 phase cell cycle arrest. In this study, we demonstrated that myostatin down-regulates Cdk4 activity via promotion of cyclin D1 degradation. Overexpression of cyclin D1 significantly blocked myostatin-induced proliferation inhibition. We further showed that phosphorylation at threonine 286 by GSK-3␤ was required for myostatin-sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
160
4
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(177 citation statements)
references
References 45 publications
10
160
4
3
Order By: Relevance
“…In this study, higher myostatin level was shown to be, in part, responsible for the muscle atrophy in Smad3-null mice. This further suggests that myostatin could signal independently of Smad3 via either Smad2 or other signaling pathways, such as p38 mitogen-activated protein kinase (MAPK), c-Jun Nterminal kinase (JNK), and phosphatidylinositol 3-kinase (PI3K) pathways as shown previously [9,[39][40][41][42]. In the present manuscript, we have provided evidence to support the critical role of Smad3 in regulation of postnatal myogenesis and SC function in mice.…”
Section: Muscle Atrophy Seen In Smad3-null Muscles Could Be Due To Insupporting
confidence: 78%
See 1 more Smart Citation
“…In this study, higher myostatin level was shown to be, in part, responsible for the muscle atrophy in Smad3-null mice. This further suggests that myostatin could signal independently of Smad3 via either Smad2 or other signaling pathways, such as p38 mitogen-activated protein kinase (MAPK), c-Jun Nterminal kinase (JNK), and phosphatidylinositol 3-kinase (PI3K) pathways as shown previously [9,[39][40][41][42]. In the present manuscript, we have provided evidence to support the critical role of Smad3 in regulation of postnatal myogenesis and SC function in mice.…”
Section: Muscle Atrophy Seen In Smad3-null Muscles Could Be Due To Insupporting
confidence: 78%
“…However, other signaling pathways including Smad2 are also shown to be involved in myostatin signaling [9,13,[39][40][41][42]. In this study, higher myostatin level was shown to be, in part, responsible for the muscle atrophy in Smad3-null mice.…”
Section: Muscle Atrophy Seen In Smad3-null Muscles Could Be Due To Inmentioning
confidence: 53%
“…The recent observation that the atrophy seen in Smad3 −/− muscles could be due to altered Mstn levels supports this idea (65). Mstn may signal independently of Smad3 via either Smad2 or other pathways such as the phosphatidylinositol 3-kinase Wnt and c-Jun N-terminal kinase pathways (66)(67)(68).…”
Section: Discussionmentioning
confidence: 95%
“…The mature myostatin dimer acts through activin type II receptor ActRIIB and to a lesser extent ActRIIA 21. The signalling involves the phosphorylation of Smad2/3 transcription factors 24, 25, and the inhibition of the PI3K/Akt pathway 26, 27. Myostatin was shown to up‐regulate the expression of p21(Waf1/Cip1), thus preventing the progression of myoblasts from the G1‐ to S‐phase of the cell cycle 28.…”
mentioning
confidence: 99%